Soft tissue dimensional change using customized titanium healing abutment in immediate implant placement in posterior teeth - Tanporn Lertwongpaisan; Parinya Amornsettachai; Woraphong Panyayong; Suphachai Suphangul (BMC, 2023)
Abstract Background The morphologic and dimensional alveolar bone is significant for resorption in the first 3 months after tooth removal because they restrict treatment outcomes with respect to function and esthetic. Following teeth extraction, the width and height of the alveolar ridge contour are reduced in both the horizontal and vertical dimensions. Following implant placement, the gingival morphology should be changed minimally compared to pre-extraction. Surrounding natural-like tissue is also an ultimate goal of the dental implant treatment, which is correlated with the cervical third contour on the anatomical tooth, for comfortable cleansing, food impaction avoidance, and esthetics. Purpose To evaluate the peri-implant soft tissue changes after immediate implant placement (IIP) with the use of a customized titanium healing abutment in the posterior teeth. Method Digital impressions using the intraoral scanner (MEDIT i500) were taken from 30 patients. Customized titanium healing abutments were designed and milled before extraction. Flapless extractions were done using surgical guides, 32 immediate implants placement were done in posterior areas, and healing abutments were placed. Soft tissues were scanned during pre-operation, and post-surgery during the 1st, 3rd, and 6th months. A 3D analysis program (Final Surface) evaluated the gingival margin distance, height, contour width, and volume in each period. SPSS was used to analyze the data with a p-value = 0.05. The between-time interval comparisons were done and the analysis was done using a Multivariate test. Results Customized titanium healing abutments used in immediate implantation maintained optimal peri-implant mucosa. In intermittent periods, there was no significant reduction in all aspects of the margin distances and heights. During the entire period, the margin height reduction on the buccal, lingual, mesial, and distal was 0.63 mm, 0.93 mm, 0.08 mm, and 0.24 mm, respectively, and contour width reduction on the buccal, lingual, and buccolingual was 0.59 mm, 0.43 mm, and 1.03 mm, respectively. There was a significant reduction in the total buccolingual contour width in the 1st month and total volume in the 3rd to 6th months. Conclusions Immediate implant placement with customized titanium healing abutment can achieve the optimal peri-implant mucosa and this protocol is an alternative for soft tissue management.